Valuable social capital: arguments supporting the need for the pastoral care profession - Dalia Rudytė (Taikomieji Moksliniai Tyrimai)
The article investigates pastoral care as a catalyst in shaping professional practice, elucidating its various realms and operational facets pertinent to the demand for spiritual guidance. As societal dynamics evolve, the imperative for pastoral intervention amplifies, paralleling the continuous expansion of demographics seeking spiritual solace. Particularly salient among the challenges confronting clients and their kin are issues surrounding aging, profound and incurable illnesses, bereavement, societal alienation, and addiction. The profession of pastoral care is portrayed as a distinctive vocation founded upon invaluable social resources, fostering cohesion among individuals sharing congruent values while fortifying interpersonal trust.